2016
DOI: 10.1002/mdc3.12423
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic “Jumpy Stump”

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…7 This patient was also depressed with suicidal ideation. 7 Parashar presented a 14-year-old male above the knee amputee who developed involuntary jerky stump movements two years after amputation. 8 The patient showed symptoms of anxiety and depression associated with his severe stump pain and jerky movements of his stump.…”
Section: Etiologymentioning
confidence: 93%
See 3 more Smart Citations
“…7 This patient was also depressed with suicidal ideation. 7 Parashar presented a 14-year-old male above the knee amputee who developed involuntary jerky stump movements two years after amputation. 8 The patient showed symptoms of anxiety and depression associated with his severe stump pain and jerky movements of his stump.…”
Section: Etiologymentioning
confidence: 93%
“…It has been conjectured that this movement disorder is caused by peripheral nerve damage associated with amputation and neuroma formation, but others have suggested that this may be a form of spinal myoclonus or conversion disorder associated with psychological or emotional trauma. 2,[5][6][7][8] In this paper, we will present a review of the current literature on etiology and treatment modalities for "jumpy stump syndrome", as well as our own experience with this unusual problem and our unique treatment approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations